Clinical presentations of adult and pediatric SARS‐CoV‐2‐positive cases in a community cohort, Nashville, Tennessee. Issue 11 (21st July 2022) - Rankin, Danielle A.; Yanis, Ahmad; Talj, Rana; Howe, Harrison L.; Bloos, Sean M.; Fernandez, Kailee N.; Amarin, Justin Z.; Bruce, Mercedes; Salib, Seifein; Hargrave, Samarian; Chappell, James D.; Spieker, Andrew J.; et al.
Abstract: Compared to adults, the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) illness in children has been lower and less severe. However, reports comparing SARS‐CoV‐2 infection among children and adults are limited. As part of our longitudinal cohort study of adults and children with SARS‐CoV‐2 infection and their household contacts in Nashville, Tennessee, we compared the clinical characteristics and outcomes of SARS‐CoV‐2 infections between children and adults. Children were more likely to be asymptomatically infected and had a shorter illness duration compared to adults. The differences observed in clinical presentation across ages may inform symptom‐specific testing, screening, and management algorithms.